The chimpanzees of Rubondo Island - Msindai, Josephine Nadezda, author.
1 online resource
Keywords: "This book tells the story of a group of chimpanzees released from captivity in Europe onto a forested island in Lake Victoria, Tanzania, about half a century ago. It combines information gathered from extensive fieldwork, laboratory and archival research. Originating from a small number of founder animals, the chimpanzee population on Rubondo island today is thriving. The authors situate their wild life within the ecological context of the island and describe the ranging behaviour of the apes, their fission-fusion-society, the architecture of constructing night nests, and their diet and gut microbiome. A comparison of the ecology, behaviour and genetics of the Rubondo apes with communities of wild chimpanzees provides exciting insights into how our closest relatives adjust to changing environments. At the same time a reconstruction of the historical circumstances that led to the Rubondo experiment reflects on its chequered colonial heritage and the operation is contextualised in the light of current threats to the survival of apes in their wild habitats. The book will be of interest to scholars and professionals working in primatology, animal behaviour, reintroduction and conservation biology"--